The New Localism, Anti-Political Development Machines, and the Role of Planning Consultants: Lessons from London's South Bank. Issue 2 (2nd April 2016) - Raco, Mike; Street, Emma; Freire-Trigo, Sonia
Abstract: This paper draws on a study of the politics of development planning in London's South Bank to examine wider trends in the governance of contemporary cities. It assesses the impacts and outcomes of so-called new localist reforms and argues that we are witnessing two principal trends. First, governance processes are increasingly dominated by anti-democratic development machines, characterized by new assemblages of public- and private-sector experts. These machines reflect and reproduce a type of development politics in which there is a greater emphasis on a pragmatic realism and a politics of delivery. Second, the presence of these machines is having a significant impact on the politics of planning. Democratic engagement is not seen as the basis for new forms of localism and community control. Instead, it is presented as a potentially disruptive force that needs to be managed by a new breed of skilled private-sector consultant. The paper examines these wider shifts in urban politics before focusing on the connections between emerging development machines and local residential and business communities. It ends by highlighting some of the wider implications of change for democratic modes of engagement and nodes of resistance in urban politics.